Correlation Between Covid-19 Pandemic and Breast Milk Production In Postpartum Mothers In Bidan Praktek Mandiri Ucu M, East Jakarta In 2021 - Triana Indrayani; Dyah Rini Cahya Ningrum; Anni Suciawati (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This research used a cross-sectional method. The sample in this research was postpartum mothers on days 1 and 2. The sampling technique used was total sampling, namely 37 postpartum mothers on day 1 and day 2. Data collection was done using a questionnaire that contained 14 questions. Based on the results of the validity test, it was obtained a value of rcount > 0.6139. This means that 14 questions in the questionnaire were declared valid. Data were then analyzed using univariate and bivariate analysis with the chi-square test to determine the correlation between COVID-19 pandemic anxiety and breast milk production in postpartum mothers at Bidan Praktek Mandiri (Independent Practice Midwife) Ucu M, in East Jakarta in 2021. The results show that there is a correlation between COVID-19 pandemic anxiety and breast milk production in postpartum mothers at Bidan Praktek Mandiri Ucu M, in East Jakarta in 2021.